The Relationship between Mindset and Reading Literacy Ability of Elementary School Students - Ni Kadek Yustika Adnyani Dewi; Kadek Yudiana (Universitas Pendidikan Ganesha, 2022)
Reading habits in Indonesian society have not developed well. In addition, the learning is carried out at this time has not been able to develop reading skills effectively and efficiently. This study aimed to analyze the mindset relationship to reading literacy ability in fifth grade elementary school students. This type of research is a correlation. The design of this research is quantitative with correlational research methods. The population in this study were all fifth-grade elementary school students, totaling 79 students. The research sample amounted to 55 students. Data collection methods used are non-test and test methods. The instrument used in collecting data are a questionnaire and reading literacy test. Data analysis techniques used are descriptive quantitative, and statistical inferential. The study results are the results of the testing hypothesis I, obtained rcount 0.757 > rtable 0.266 then H0 is rejected, which means it is significant. Hypothesis II test results, rcount 0.434 > rtable 0.266 then H0 is rejected, which means it is significant. So that the Growth mindset has a relationship with the reading literacy ability of fifth-grade elementary school students. A fixed mindset also positively impacts students' reading literacy skills. It was concluded that there was a significant correlation between mindset and reading literacy ability.